CXCL8 expression is associated with advanced stage, right sidedness, and distinct histological features of colorectal cancer - Kathryn AF Pennel; Jean A Quinn; Colin Nixon; Jitwadee Inthagard; Hester C vanWyk; David Chang; Selma Rebus; GPOL Group; Jennifer Hay; Noori N Maka; Campbell SD Roxburgh; Paul G Horgan; et al. (Wiley, 2022)
Abstract CXCL8 is an inflammatory chemokine elevated in the colorectal cancer (CRC) tumour microenvironment. CXCR2, the major receptor for CXCL8, is predominantly expressed by neutrophils. In the cancer setting, CXCL8 plays important roles in neutrophil chemotaxis, facilitating angiogenesis, invasion, and metastasis. This study aimed to assess the spatial distribution of CXCL8 mRNA expression in CRC specimens, explore associations with clinical characteristics, and investigate the underlying biology of aberrant CXCL8 levels. CXCR2 expression was also assessed in a second cohort of unique CRC primary tumours and synchronously resected matched liver metastases. A previously constructed tissue microarray consisting of a cohort of stage I-IV CRC patients undergoing surgical resection with curative intent (n = 438) was probed for CXCL8 via RNAscope®. Analysis was performed using HALO® digital pathology software to quantify expression in the tumour and stromal compartments. Scores were assessed for association with clinical characteristics. Mutational analyses were performed on a subset of these patients to determine genomic differences in patients with high CXCL8 expression. A second cohort of stage IV CRC patients with primary and matched metastatic liver tumours was stained via immunohistochemistry for CXCR2, and scores were assessed for clinical significance. CXCL8 expression within the stromal compartment was associated with reduced cancer‐specific survival in the first cohort (p = 0.035), and this relationship was potentiated in right‐sided colon cancer cases (p = 0.009). High CXCL8 within the stroma was associated with driving a more stromal‐rich phenotype and the presence of metastases. When stromal CXCL8 scores were combined with tumour‐infiltrating macrophage counts or systemic neutrophil counts, patients classified as high for both markers had significantly poorer prognosis. CXCR2+ immune cell infiltration was associated with increased stromal invasion in liver metastases (p = 0.037). These data indicate a role for CXCL8 in driving unfavourable tumour histological features and promoting metastases. This study suggests that inhibiting CXCL8/CXCR2 should be investigated in patients with right‐sided colonic disease and stroma‐rich tumours.